College study skills : - Blerkom, Dianna L. Van (Thomson Wadsworth, 2006)
College Study Skills provides both the guidance and the hands-on exercises needed to help students improve their ability to learn in the university setting. Chapters on adjusting to college, setting goals, improving memory and concentration, and managing time complement those dealing with more concrete skills such as reading, note-taking, highlighting, preparing for exams, and taking essay tests. In addition to clearly explaining different learning strategies, each chapter also includes useful examples as well as practice activities and self-evaluation techniques.